Mineral fertilization in tropical reforestation: seedling growth and survival of ten native tree species in Tabasco, Mexico - Martínez Bravo, René Davíd; Ricker, Martin; Nava-Cruz, Yolanda; Siebe, Christina (Instituto de Ecología, A.C., 2022)
A reforestation trial was carried out with ten native tree species under four different doses of mineral fertilizer in the lowland tropics in Tabasco, Mexico. In six one-hectare plots, 2415 seedlings of Brosimum alicastrum, Calophyllum brasiliense, Ceiba pentandra, Colubrina arborescens, Diphysa americana, Enterolobium cyclocarpum, Handroanthus chrysanthus, Pimenta dioica, Pouteria sapota, and Tabebuia rosea were planted in a randomized design. The mineral fertilizer consisted of a single initial dose of 0 g, 150 g, 375 g or 750 g nitrogen-phosphorus-potassium (NPK), as well as micronutrients (Ca, Cu, Fe, Mg, Mn, Zn, S). First-year survival and median height increment of transplanted seedlings were analyzed with statistical confidence intervals. Whereas overall first-year survival for Ceiba pentandra for all fertilization doses combined was 66%, it was only 12% for Brosimum alicastrum. On the other hand, median height increment was 102 cm for Enterolobium cyclocarpum, whereas it was only 7 cm for Pimenta dioica. The survival of six of the planted species was apparently affected by the salinity effect caused by mineral fertilization. The only species that benefited from mineral fertilization in a statistically significant way was C. pentandra. In conclusion, mineral fertilization in tropical reforestation is not recommended in general. Appropriate species selection is far more important for favorable survivorship and height increment.